2009
DOI: 10.3357/asem.2535.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low Contrast Acuity at Photopic and Mesopic Luminance Under Mild Hypoxia, Normoxia, and Hyperoxia

Abstract: Mild hypoxia degrades low contrast acuity progressively with decreasing mesopic luminance. At 0.1 cd x m(-2), supplementary oxygen enhances low contrast acuity, implying that visual performance is oxygen-dependent in the mid-mesopic range. Relative to performance under mild hypoxia at 3048 m (10,000 ft), supplementary oxygen can extend functionally useful vision to lower light levels. The findings are relevant to contemporary military night flying, viewing the external scene directly or through night vision de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…As pointed out recently [45], it is important to have sensitive and objective criteria that experts can use to decide whether small changes in vision in older subjects can be attributed entirely to normal aging or reflect early signs of retinal pathology. Since visual performance at lower light levels is more compromised in patients with early signs of ocular pathology [4] and the effects of mild acute hypoxia in normal subjects are also more detectable at lower light levels [5,6,46,47], it may be desirable to assess changes in visual performance over a range of light levels and not just photopic vision under optimum conditions. Indeed, if the HR index does reflect retinal susceptibility to disease, and hence hypoxia, imposed mild systemic hypoxia may exacerbate the loss of chromatic sensitivity as reflected in the HR index , more so in older subjects and/or those with more severe damage to the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out recently [45], it is important to have sensitive and objective criteria that experts can use to decide whether small changes in vision in older subjects can be attributed entirely to normal aging or reflect early signs of retinal pathology. Since visual performance at lower light levels is more compromised in patients with early signs of ocular pathology [4] and the effects of mild acute hypoxia in normal subjects are also more detectable at lower light levels [5,6,46,47], it may be desirable to assess changes in visual performance over a range of light levels and not just photopic vision under optimum conditions. Indeed, if the HR index does reflect retinal susceptibility to disease, and hence hypoxia, imposed mild systemic hypoxia may exacerbate the loss of chromatic sensitivity as reflected in the HR index , more so in older subjects and/or those with more severe damage to the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Vision at low light levels is also compromised by imposed mild levels of hypoxia in healthy young subjects [5,6]. Other studies have shown that healthy normal observers who are carriers of the CFH, LOC387715, and HRTA1 genotypes and are considered to be of high risk of developing age-related maculopathy later in life perform significantly worse in the mesopic range in some visual tasks, but not at higher light levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the color discrimination losses along the tritan axis at higher altitudes, the Nagel anomaloscope settings tend to require more green to match yellow, and there may be a relative decrease in the sensitivity to green light when measured using heterochromatic flicker photometry, especially at conditions equivalent to altitudes above 4000 m [2][3][4][5][6]11]. It is not clear whether detection thresholds for blue and green lights are affected more than the thresholds for red lights at altitudes less than 4000 m; however, it is unequivocal that detection and contrast thresholds for all colored lights are elevated in mesopic and scotopic light conditions before photopic conditions [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the spatial contrast sensitivity function (for larger, longer-duration sinusoidal gratings) appears more resistant to changes in oxygenation, at least until background luminance becomes much dimmer ( 11 ). The benefi t of 100% oxygen to enhance low contrast acuity ( 12 ) and fl icker sensitivity ( 15 ) at mesopic luminance, relative to normoxia (breathing air near sea level), implies that cone photoreceptor-mediated vision becomes oxygen-limited at moderate twilight luminance under normal respiratory conditions. Thus, supplementary oxygen might enhance cone-dominant, upper mesopic visual sensitivity, especially under conditions of high metabolic demand (e.g., rapid adaptation to fl uctuating retinal illumination), just as hyperoxia enhances rod photoreceptor metabolism, hastening scotopic adaptation to the dark at sea level ( 14 ).…”
mentioning
confidence: 98%
“…M ILD SYSTEMIC HYPOXIA, equivalent to breathing air at 10,000 ft (3048 m), induces progressively greater loss of visual sensitivity as light levels fall in the upperto-mid mesopic range, with decrements affecting color discrimination ( 13 ), low contrast acuity ( 12 ), and dynamic contrast fl icker ( 15 ). On the other hand, the spatial contrast sensitivity function (for larger, longer-duration sinusoidal gratings) appears more resistant to changes in oxygenation, at least until background luminance becomes much dimmer ( 11 ).…”
mentioning
confidence: 99%